37.3k views
2 votes
Need help, explaining this to me

Need help, explaining this to me-example-1
User Errorseven
by
5.6k points

1 Answer

5 votes

\begin{gathered} (-3p+9)+(-7-p+2p^2)\text{ Given} \\ \\ \text{First, simplify by taking out the parenthesis and making sure it stays true to the operation} \\ \rightarrow-3p+9-7-p+2p^2 \\ \text{Next, arrange starting from the highest degree }(p^2)\text{ to the constant},\text{ and group them} \\ p^2\rightarrow p\rightarrow\text{constant} \\ 2p^2-3p-p+9-7\text{ (final answer)} \end{gathered}

User Mithlesh Kumar
by
5.4k points